2017
DOI: 10.5812/iranjradiol.61846
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Preinvasive from Invasive Lung Adenocarcinoma Appearing as Part-Solid Ground-Glass Nodule Using CT Value and Solid-Part Diameter

Abstract: Objectives: To evaluate the differentiating roles of computed tomography (CT) for invasive adenocarcinomas (IACs) of the lung from preinvasive lesions or minimally invasive adenocarcinomas (MIAs) manifesting as part-solid ground-glass nodules (GGNs). Patients and Methods: All 230 lesions were pathologically confirmed. Their size, CT parameters and morphological features were compared among the three groups. Optimal cut-off values were calculated for parameters with diagnostic value. Results: The diameter of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…According to a study by Oda et al [15] , the occurrence rate of spicule sign in IAC was higher than that in PIL, the difference was statistically signi cant. Wang et al [16] reported that the incidence of pleural traction sign, lobulation sign, bronchial cut-off sign, air bronchogram sign and spicule sign in IAC was signi cantly higher than that in MIA and PIL, while there was no signi cant difference in cavity sign among the three groups. In our research there was no signi cant difference in the distribution of vacuole sign in PIL, MIA and IAC, but the incidence of cavity sign in IAC was higher than that in the other two groups, and the difference was statistically signi cant(P<0.01).…”
Section: Discussionmentioning
confidence: 98%
“…According to a study by Oda et al [15] , the occurrence rate of spicule sign in IAC was higher than that in PIL, the difference was statistically signi cant. Wang et al [16] reported that the incidence of pleural traction sign, lobulation sign, bronchial cut-off sign, air bronchogram sign and spicule sign in IAC was signi cantly higher than that in MIA and PIL, while there was no signi cant difference in cavity sign among the three groups. In our research there was no signi cant difference in the distribution of vacuole sign in PIL, MIA and IAC, but the incidence of cavity sign in IAC was higher than that in the other two groups, and the difference was statistically signi cant(P<0.01).…”
Section: Discussionmentioning
confidence: 98%